Nitrogen-doped carbon-loaded iron material for adsorbing BPA and preparation method of nitrogen-doped carbon-loaded iron material

Through the synthesis of nitrogen-doped carbon-loaded iron materials, the problems of small BPA adsorption capacity, slow rate and poor stability in the prior art are solved, and efficient, fast and stable BPA adsorption effect is achieved.

CN120205088APending Publication Date: 2025-06-27XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510279662.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The prior art cannot effectively remove BPA, with small adsorption capacity, slow adsorption rate and poor stability, resulting in BPA still remaining in sewage treatment, which harms the environment and organisms.

Method used

Nitrogen-doped carbon-supported iron material is used, and the ZIF-8 precursor is doped with Fe, and pyrolytic synthesis is carried out under a nitrogen atmosphere to form a material with high adsorption capacity and fast adsorption rate.

Benefits of technology

The maximum adsorption amount of BPA in the water at room temperature reached 877.45 mg·g-1, with a fast adsorption rate, a removal rate within 10 minutes is greater than 90%, and has good adsorption stability and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120205088A_ABST
    Figure CN120205088A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon-loaded iron material for adsorbing BPA and a preparation method thereof, and the method comprises the following steps: 1, dissolving 1.116 g of Zn (NO3) 3.6 H2O and 0.15-0.25 g of Fe (NO3) 3.9 H2O in 100 mL of absolute methanol, and uniformly stirring to obtain a solution A; 2, dissolving 2.608 g of 2-methylimidazole in 100 mL of absolute methanol, and uniformly stirring to obtain a solution B; 3, pouring the solution A into the solution B, stirring and centrifugally separating out a precipitate under a closed condition, and sequentially washing, drying and grinding to obtain a faint yellow powdery Fe-doped ZIF-8 precursor marked as ZIF-8 / Fe; and 4, putting the ZIF-8 / Fe into a tubular furnace, heating from room temperature to 900-1000 DEG C in an N2 atmosphere at a heating rate of 2-5 DEG C / min, pyrolyzing for 3-4 hours, cooling, and grinding to obtain a black powdery nitrogen-doped carbon-loaded iron material, namely Fe-N-C. The invention also discloses a preparation method of the nitrogen-doped carbon-loaded iron material. The prepared Fe-N-C has good adsorption performance on BPA, the maximum adsorption capacity at the normal temperature is 877.45 mg.g <-1 >, and in the adsorption process of 10 min, the removal rate of BPA in a water body reaches up to 90% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wastewater treatment, and particularly relates to a nitrogen-doped carbon-supported iron material for adsorbing BPA and a preparation method thereof. Background Art

[0002] Bisphenol A (BPA) is a typical endocrine disruptor and environmental estrogen, with low concentration and high toxicity. On the one hand, as an environmental endocrine disruptor, it acts on the body in the form of hormones, interfering with human endocrine and metabolic activities, causing human metabolic disorders, and triggering metabolic syndromes such as diabetes, hyperlipidemia, and hypertension. On the other hand, as an alkyl environmental estrogen, it interferes with the synthesis, transport, and metabolism of natural estrogens, affecting the functions of the human reproductive system, embryonic and nervous system development.

[0003] As an important industrial raw material, BPA is commonly used in the synthesis of materials such as epoxy resins and polycarbonate plastics, and can be used as a product additive for producing plasticizers, flame retardants, heat stabilizers, etc. With the continuous expansion of production and application scope, the annual emission of BPA exceeds hundreds of tons and is widely distributed in the environment. BPA has been detected in water bodies, soil, sediments, air, municipal solid waste, drinking water, and food samples in multiple river basins. Table 1 shows the concentration data of BPA in environmental water bodies in different regions of China. It can be seen that the detection rate of BPA is relatively high, and it has become a pollutant that cannot be ignored in environmental water bodies in China.

[0004] Table 1 Concentration of BPA in water bodies in different regions of China

[0005]

[0006] Note: nd means not detected / below the detection limit, not detected.

[0007] At present, a variety of water treatment technologies for BPA have been developed and reported, including photocatalysis, ozonation, electrochemical oxidation, membrane technology, biodegradation, and adsorption, etc. Among them: The photocatalysis technology is a reaction process in which organic pollutants are oxidized and degraded under the action of visible light or ultraviolet light. Due to the limitations of reaction conditions, the photochemical oxidation and degradation are often not thorough enough, and a variety of aromatic organic intermediates are easily generated; Ozonation refers to the method of using ozone as an oxidant to purify and disinfect wastewater. However, ozone is not easy to store and needs to be prepared on-site, resulting in a relatively high treatment cost of ozonation; Membrane bioreactors and nanofiltration membranes have the ability to decompose and eliminate many endocrine-disrupting compounds including BPA. However, over time, the pore size of the membrane material is easily blocked, and the filtration efficiency shows a downward trend; The adsorption method has the advantages of low cost, fast removal speed, and high efficiency, and is widely used. However, traditional materials for adsorbing BPA have a small adsorption capacity, and the maximum adsorption amount at room temperature is only about 300 mg·g -1 or so, and the adsorption rate is slow and the stability is poor. In short, the current sewage treatment methods cannot completely remove BPA, and there is still a small amount of BPA residue in the reclaimed water. If it is released into the natural environment and migrates and transforms, it will cause harm to sensitive receptors and organisms in the surrounding environment. Therefore, the development of efficient, green, and economical BPA treatment technologies is the focus of research. In particular, it is of great significance to develop an adsorbent material for BPA with a large adsorption capacity, a fast adsorption rate, and strong stability. Summary of the Invention

[0008] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a nitrogen-doped carbon-supported iron material for adsorbing BPA and its preparation method, which has good adsorption performance and adsorption stability for BPA.

[0009] In order to achieve the above purpose, the present invention adopts the following technical solutions to implement:

[0010] A preparation method of a nitrogen-doped carbon-supported iron material for adsorbing BPA, comprising the following steps:

[0011] Step 1: Dissolve 1.116 g of Zn(NO3)3·6H2O and 0.15 - 0.25 g of Fe(NO3)3·9H2O in 100 mL of anhydrous methanol, stir evenly to obtain solution A;

[0012] Step 2: Dissolve 2.608 g of 2-methylimidazole in 100 mL of anhydrous methanol, stir evenly to obtain solution B;

[0013] Step 3: Pour solution A into solution B, stir under closed conditions, centrifuge to separate the precipitate, wash, dry, and grind in sequence to obtain a pale yellow powdery Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe;

[0014] Step 4: Place the ZIF-8 / Fe into a tubular furnace. Under a N2 atmosphere, with a heating rate of 2 - 5 °C / min, heat from room temperature to 900 - 1000 °C, pyrolyze for 3 - 4 h, cool, and then grind to obtain a black powder of nitrogen-doped carbon-supported iron material, denoted as Fe-N-C.

[0015] Further, the stirring time in both Step 1 and Step 2 is 10 - 30 min.

[0016] Further, the stirring time in Step 3 is 2 - 3 h.

[0017] Further, the centrifugation in Step 3 is carried out using a centrifuge at a rate of 5000 rpm for 10 min.

[0018] Further, the centrifugal washing in Step 3 is carried out using a centrifuge at a rate of 5000 rpm. Wash the precipitate 4 - 5 times with anhydrous methanol, with each wash lasting 10 min.

[0019] Further, the drying in Step 3 is carried out in an oven at 60 °C for 12 h.

[0020] A nitrogen-doped carbon-supported iron material for adsorbing BPA has a maximum adsorption capacity for BPA in water of 877.45 mg·g -1 .

[0021] Further, for the nitrogen-doped carbon-supported iron material used to adsorb BPA, in a 10-min adsorption process, the removal rate of BPA in water is greater than 90%.

[0022] Compared with the prior art, the present invention has the following technical effects:

[0023] 1), The present invention uses C-rich ZIF-8 as a precursor. With the help of the good framework structure brought by its unique three-dimensional dodecahedron structure, first introduce Fe for doping modification, and then, under a nitrogen atmosphere, directly pyrolyze to synthesize a new nitrogen-doped carbon-supported iron material, maintaining the regular rhombic dodecahedron structure of ZIF-8. At room temperature, the maximum adsorption capacity for BPA in water reaches 877.45 mg·g -1 , far higher than 300 mg·g of the prior art -1 , and moreover, in a 10-min adsorption process, the removal rate of BPA in water is as high as over 90%, with a relatively fast adsorption rate; In short, the nitrogen-doped carbon-supported iron material prepared by the present invention has the advantages of large adsorption capacity and fast adsorption rate, and can efficiently remove BPA in water.

[0024] 2) In the process of preparing the Fe-doped ZIF-8 precursor of the present invention, zinc ions are introduced first, and then pyrolysis is carried out at a temperature not lower than 900 °C to evaporate zinc atoms, thereby forming more vacancy adsorption sites. At the same time, considering that the electronegativity of nitrogen atoms is higher than that of carbon, therefore, a nitrogen-doped carbon material is generated by pyrolysis in a nitrogen environment. By doping nitrogen, the rearrangement of the electron distribution of carbon atoms is caused, increasing the surface polarity of the material, making it easier to adsorb polar molecules, and thus improving the adsorption performance of BPA.

[0025] 3) By simulating the real water environment with tap water, it is found that the nitrogen-doped carbon-supported iron material prepared by the present invention has good adsorption performance for BPA in the real water environment. Moreover, through multiple cyclic adsorption experiments, it is found that the nitrogen-doped carbon-supported iron material has good adsorption stability for BPA. After each adsorption, almost complete desorption of BPA can be achieved, improving the effective recovery of BPA and having considerable practical application potential. Brief Description of the Drawings

[0026] Figure 1 : XRD patterns of the nitrogen-doped carbon-supported iron material and ZIF-8 / Fe prepared in Example 1 of the present invention;

[0027] Figure 2 : FTIR spectra of the nitrogen-doped carbon-supported iron material and ZIF-8 / Fe prepared in Example 1 of the present invention;

[0028] Figure 3 : SEM image of the nitrogen-doped carbon-supported iron material prepared in Example 1 of the present invention;

[0029] Figure 4 : EDS-Mapping image of the nitrogen-doped carbon-supported iron material prepared in Example 1 of the present invention;

[0030] Figure 5 : Adsorption amount change curves of the nitrogen-doped carbon-supported iron material prepared in Example 1 of the present invention for low-concentration BPA in pure water and tap water;

[0031] Figure 6 : Isothermal adsorption Langmuir model fitting curves of the nitrogen-doped carbon-supported iron materials prepared in Examples 1 to 4 of the present invention for BPA in water;

[0032] Figure 7 : Bar chart of the change in the adsorption amount of the nitrogen-doped carbon-supported iron material prepared in Example 1 of the present invention for BPA in tap water under different cycle numbers;

[0033] Figure 8 : Bar chart of the change in the desorption amount of the nitrogen-doped carbon-supported iron material prepared in Example 1 of the present invention for BPA in tap water under different cycle numbers. Detailed Description of the Invention

[0034] The following further elaborates on the specific content of the present invention in conjunction with embodiments.

[0035] Example 1

[0036] Step 1: Dissolve 1.116 g of Zn(NO3)3·6H2O and 0.2 g of Fe(NO3)3·9H2O in 100 mL of methanol, stir for 10 min to obtain solution A;

[0037] Step 2: Dissolve 2.608 g of 2-methylimidazole in 100 mL of methanol, stir for 10 min to obtain solution B;

[0038] Step 3: Pour solution A into solution B, under closed conditions, stir for 2 h. First, use a centrifuge with a speed of 5000 rpm to centrifuge for 10 min to separate the precipitate. Then, use a centrifuge with a speed of 5000 rpm and wash the precipitate 5 times with anhydrous methanol, each time for 10 min. Then, dry in an oven at 60 °C for 12 h, and finally grind to obtain a light yellow powder-like Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe;

[0039] Step 4: Place ZIF-8 / Fe in a tube furnace, under a N2 atmosphere, with a heating rate of 5 °C / min, heat from room temperature to 900 °C, pyrolyze for 3 h, and after cooling, obtain a black powder-like nitrogen-doped carbon-supported iron material, denoted as Fe-N-C.

[0040] Using a SHIMADZ 6100 type multi-crystal rotating anode X-ray diffractometer, with a Ni filter, tube current of 20 mA, tube voltage of 20 kV, scanning angle 2θ = 10 - 80°, scanning speed 8°·min -1 Perform X-ray diffraction on the ZIF-8 / Fe and nitrogen-doped carbon-supported iron material Fe-N-C prepared in Example 1 to obtain the XRD pattern as Figure 1 shown. Among them: As can be seen from Figure 1 (a), the diffraction peak positions of the synthesized ZIF-8 / Fe precursor at 10.4°, 12.7°, 14.7°, 16.4°, 18.0°, 24.5°, and 26.7° coincide with the diffraction peaks of ZIF-8 in the literature, indicating that ZIF-8 with relatively high crystallinity has been successfully synthesized. The remaining miscellaneous peaks are attributed to the trace Fe present in the material; As can be seen from Figure 1 (b), the Fe-N-C obtained after pyrolysis loses the characteristic peaks of ZIF-8 and two broad peaks appear, indicating that a graphitized carbon material is formed after pyrolysis. In addition, no characteristic peaks of iron oxide are observed, indicating that the Fe in Fe-N-C is dispersed in the material in the form of a single substance.

[0041] The ZIF-8 / Fe precursor prepared in Example 1 and the iron-nitrogen-doped carbon-supported iron material Fe-N-C were analyzed by infrared spectroscopy using a Nexus 870 Fourier transform infrared spectrometer. The FT-IR spectral results obtained are as Figure 2 shown. It can be seen that for the precursor ZIF-8 / Fe before pyrolysis, characteristic absorption peaks consistent with those of ZIF-8 already reported in the literature were shown. Among them, the broad peak between 3500 cm -1 and 3200 cm -1 corresponds to the stretching of the N-H bond. The absorption peaks at 3134 cm -1 and 2928 cm -1 are attributed to the stretching vibration peaks of the C-H bonds in the methyl group and imidazole ring respectively. The absorption peak at 1590 cm -1 corresponds to the stretching of the C=N bond, while the strong peaks at 1424 cm -1 and 1307 cm -1 correspond to the stretching of the entire ring. The several spectral bands appearing in the range of 1350 cm -1 to 900 cm -1 are due to the in-plane bending of the ring, and the absorption peaks at 757 cm -1 and 690 cm -1 are related to the aromatic sp 2 C-H bending, indicating the successful synthesis of ZIF-8. After pyrolysis, the characteristic peaks of ZIF-8 all disappeared, only showing irregular broad peaks, indicating that complete graphitization had occurred at this time, forming the iron-nitrogen-doped carbon-supported iron adsorption material Fe-N-C.

[0042] The iron-nitrogen-doped carbon-supported iron material prepared in Example 1 was analyzed by scanning electron microscopy using a Gemini 500 type scanning electron microscope. The results of the scanning electron microscopy (SEM) obtained are as Figure 3 shown. It can be seen that the Fe-N-C prepared after pyrolysis maintained the typical rhombic dodecahedron morphology of ZIF-8 itself, indicating that the pyrolysis process did not cause the structural collapse of ZIF-8, and the particle size was small, corresponding to a large specific surface area, endowing the material with good adsorption potential.

[0043] From Figure 4 the EDS energy spectrum, it can be seen that the main elements present in the material are C, a small amount of N element and trace amounts of Fe element are evenly dispersed on the skeleton of Fe-N-C. Since the boiling point of Zn is 907 °C, during the pyrolysis process, all Zn has volatilized. The O element is mainly attributed to the oxygen in the environment adsorbed on the surface of the material during the testing process.

[0044] First, load 47.5 mL of ultrapure water into a beaker, then add 0.002 g of the Fe-N-C prepared in Example 1. Seal the beaker with a sealing film and place it in an ultrasonic machine for ultrasonic dispersion for 10 min. Transfer the beaker to a 25 °C constant temperature water bath and stir. Then, add 2.5 mL of 15 mmol·L -1 BPA stock solution to start the adsorption reaction. During the reaction process, use a pipette to take reaction solution samples at different times, and filter the reaction solution samples through a 0.45 μm polyethersulfone filter membrane. Then, use an HPLC high performance liquid chromatograph to measure the BPA concentration in the samples. All experiments are repeated three times to reduce errors. According to the detection results, an isothermal adsorption curve is plotted. The results are as Figure 6 shown. It is found that the adsorption process of BPA by the Fe-N-C prepared in Example 1 conforms to the Langmuir model, indicating that the adsorption process is monolayer adsorption. Moreover, at 25 °C, 0.04 g·L -1 of the nitrogen-doped carbon supported iron material Fe-N-C adsorbs 171.2 mg·L -1 of BPA. After 3 h of adsorption equilibrium, the maximum adsorption capacity is 877.45 mg·g -1 , and the removal rate of BPA in water reaches 91.3% during the 10-min adsorption process, showing a good adsorption effect.

[0045] In addition, to verify the influence of various ions in real water bodies on the adsorption effect of Fe-N-C, take two portions of 0.002 g

[0046] of the Fe-N-C prepared in Example 1 and add them to two beakers containing 47.5 mL of tap water and 47.5 mL of pure water respectively. Seal the two beakers with a sealing film and place them in an ultrasonic machine for ultrasonic dispersion for 10 min. Transfer the beakers to a 25 °C constant temperature water bath and stir. Then, add 2.5 mL of 1 mmol·L -1 BPA stock solution to start the adsorption reaction. During the reaction process, use a pipette to take reaction solution samples at different times, and filter the reaction solution samples through a 0.45 μm polyethersulfone filter membrane. Then, use an HPLC high performance liquid chromatograph to measure the BPA concentration in the samples. All experiments are repeated three times to reduce errors. According to the detection results, a curve of adsorption capacity versus time is plotted, as Figure 5 shown. Whether in pure water or tap water conditions, at 25 °C, 0.04 g·L -1 of the nitrogen-doped carbon supported iron material Fe-N-C adsorbs 11.4 mg·L -1 of BPA. After 3 h of adsorption equilibrium, the maximum adsorption capacity is 281 mg·g -1, and at 10 min, the removal rate of BPA in water reached 91.2%, showing good adsorption effect. This indicates that the removal effect of Fe-N-C on BPA in water is not affected by various ions in the environment and has good stability.

[0047] See Figure 7 , at [Fe-N-C] = 0.04 g·L -1 ; [BPA] = 0.05 mM, T = 298 K, the change of the removal rate of BPA in water by Fe-N-C prepared in Example 1 in tap water with the number of adsorption cycles was measured. It can be seen that the removal rate of Fe-N-C for BPA only decreased by 25% after five cycles; See Figure 8 , it can be seen that almost every cycle can be completely desorbed, and the effective recovery of BPA can be achieved, with great potential for repeated application.

[0048] Example 2

[0049] Step 1: Dissolve 1.116 g of Zn(NO3)3·6H2O and 0.15 g of Fe(NO3)3·9H2O in 100 mL of methanol, stir for 20 min to obtain solution A;

[0050] Step 2: Dissolve 2.608 g of 2-methylimidazole in 100 mL of methanol, stir for 20 min to obtain solution B;

[0051] Step 3: Pour solution A into solution B, stir for 3 h under closed conditions. First, use a centrifuge at a speed of 5000 rpm for 10 min to separate the precipitate. Then, use a centrifuge at a speed of 5000 rpm and wash the precipitate 4 times with anhydrous methanol, 10 min each time. Then, dry in an oven at 60 °C for 12 h, and finally grind to obtain a light yellow powdery Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe;

[0052] Step 4: Put ZIF-8 / Fe into a tubular furnace, under N2 atmosphere, with a heating rate of 2 °C / min, heat up from room temperature to 1000 °C, pyrolyze for 3 h, and after cooling, obtain a black powdery iron material supported by nitrogen-doped carbon, denoted as Fe-N-C.

[0053] First, put 47.5 mL of ultrapure water into a beaker, then add 0.002 g of Fe-N-C prepared in Example 2, seal the beaker with a sealing film and put it into an ultrasonic machine for ultrasonic dispersion for 10 min. Transfer the beaker to a 15 °C constant temperature water bath and stir. Then, add 2.5 mL of 15 mmol·L -1BPA stock solution was used to start the adsorption reaction. During the reaction process, pipettes were used to take reaction solution samples at different times, and the reaction solution samples were filtered through a 0.45 μm polyethersulfone filter membrane. Then, an HPLC high-performance liquid chromatograph was used to measure the BPA concentration in the samples. All experiments were repeated three times to reduce errors. An isothermal adsorption curve was plotted based on the detection results. The results are as Figure 6 shown. It was found that the adsorption process of BPA by Fe-N-C prepared in Example 2 conforms to the Langmuir model, indicating that the adsorption process is monolayer adsorption. Moreover, in a 15 °C environment, 0.04 g·L -1 The nitrogen-doped carbon-supported iron material Fe-N-C adsorbed 171.2 mg·L -1 of BPA. After 3 h of adsorption equilibrium, the maximum adsorption capacity was 977.36 mg·g -1 , and in the 10-min adsorption process, the removal rate of BPA in water reached 90.5%, showing a good adsorption effect.

[0054] Example 3

[0055] Step 1: Dissolve 1.116 g of Zn(NO3)3·6H2O and 0.25 g of Fe(NO3)3·9H2O in 100 mL of methanol, and stir for 30 min to obtain solution A;

[0056] Step 2: Dissolve 2.608 g of 2-methylimidazole in 100 mL of methanol, and stir for 30 min to obtain solution B;

[0057] Step 3: Pour solution A into solution B, and under airtight conditions, stir for 3 h. First, use a centrifuge at a speed of 5000 rpm to centrifuge for 10 min to separate the precipitate. Then, use a centrifuge at a speed of 5000 rpm and wash the precipitate 5 times with anhydrous methanol, 10 min each time. Then, use an oven at 60 °C to dry for 12 h, and finally grind to obtain a pale yellow powdery Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe;

[0058] Step 4: Place ZIF-8 / Fe in a tubular furnace. Under a N2 atmosphere, with a heating rate of 3 °C / min, heat from room temperature to 900 °C and pyrolyze for 4 h. After cooling, a black powdery nitrogen-doped carbon-supported iron material is obtained, denoted as Fe-N-C.

[0059] First, load 47.5 mL of ultrapure water into a beaker, then add 0.002 g of Fe-N-C prepared in Example 3, seal the beaker with a sealing film and place it in an ultrasonic machine for ultrasonic dispersion for 10 min. Transfer the beaker to a 35 °C constant temperature water bath and stir. Then, add 2.5 mL of 15 mmol·L -1BPA stock solution was used to start the adsorption reaction. During the reaction process, pipettes were used to take reaction solution samples at different times, and the reaction solution samples were filtered through a 0.45 μm polyethersulfone filter membrane. Then, an HPLC high-performance liquid chromatograph was used to measure the BPA concentration in the samples. All experiments were repeated three times to reduce errors. An isothermal adsorption curve was plotted based on the detection results. The results are as Figure 6 shown. It was found that the adsorption process of BPA by Fe-N-C prepared in Example 3 conforms to the Langmuir model, indicating that the adsorption process is a monolayer adsorption. Moreover, in an environment of 35 °C, 0.04 g·L -1 The nitrogen-doped carbon-supported iron material Fe-N-C adsorbed 171.2 mg·L -1 of BPA. After 3 h of adsorption equilibrium, the maximum adsorption capacity was 782.41 mg·g -1 , and in the 10-min adsorption process, the removal rate of BPA in water reached 91.1%, showing a good adsorption effect.

[0060] Example 4

[0061] Step 1: Dissolve 1.116 g of Zn(NO3)3·6H2O and 0.18 g of Fe(NO3)3·9H2O in 100 mL of methanol and stir for 15 min to obtain solution A;

[0062] Step 2: Dissolve 2.608 g of 2-methylimidazole in 100 mL of methanol and stir for 15 min to obtain solution B;

[0063] Step 3: Pour solution A into solution B, and under airtight conditions, stir for 2.5 h. First, use a centrifuge at a speed of 5000 rpm to centrifuge for 10 min to separate the precipitate. Then, use a centrifuge at a speed of 5000 rpm and wash the precipitate 4 times with anhydrous methanol, 10 min each time. Then, use an oven at 60 °C to dry for 12 h, and finally grind to obtain a pale yellow powdery Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe;

[0064] Step 4: Place ZIF-8 / Fe in a tubular furnace. Under a N2 atmosphere, with a heating rate of 4 °C / min, heat from room temperature to 950 °C and pyrolyze for 3.5 h. After cooling, a black powdery nitrogen-doped carbon-supported iron material is obtained, denoted as Fe-N-C.

[0065] First, put 47.5 mL of ultrapure water into a beaker, then add 0.002 g of Fe-N-C prepared in Example 4, seal the beaker with a sealing film and put it into an ultrasonic machine for ultrasonic dispersion for 10 min. Transfer the beaker to a 45° constant temperature water bath and stir. Then, add 2.5 mL of 15 mmol·L -1BPA stock solution was used to start the adsorption reaction. During the reaction process, pipettes were used to take reaction solution samples at different times, and the reaction solution samples were filtered through a 0.45 μm polyethersulfone membrane. Then, an HPLC high performance liquid chromatograph was used to measure the BPA concentration in the samples. All experiments were repeated three times to reduce errors. An isothermal adsorption curve was plotted based on the detection results. The results are as follows: Figure 6 As shown, it was found that the adsorption process of BPA by the Fe-N-C prepared in Example 4 conforms to the Langmuir model, indicating that the adsorption process is monolayer adsorption. Moreover, in an environment of 45 °C, 0.04 g·L -1 The nitrogen-doped carbon-supported iron material Fe-N-C adsorbed 171.2 mg·L -1 of BPA. After 3 h of adsorption equilibrium, the maximum adsorption capacity was 680.34 mg·g -1 , and in the 10-min adsorption process, the removal rate of BPA in water reached 91.6%, showing good adsorption performance.

Claims

1. A method for preparing a nitrogen-doped carbon-loaded iron material for adsorbing BPA, characterized in that: The steps include: Step 1, dissolve 1.116 g Zn(NO3)3·6H2O and 0.15-0.25 g Fe(NO3)3·9H2O in 100 mL anhydrous methanol, stir evenly, and obtain solution A; Step 2, dissolve 2.608 g of 2-methylimidazole in 100 mL of anhydrous methanol and stir evenly to obtain solution B; Step 3, pouring solution A into solution B, stirring under closed conditions, centrifuging to separate the precipitate, washing, drying and grinding in sequence to obtain a light yellow powdery Fe-doped ZIF-8 precursor, denoted as ZIF-8 / Fe; Step 4: Place ZIF-8 / Fe in a tubular furnace, heat from room temperature to 900°C to 1000°C at a heating rate of 2 to 5°C / min under a N2 atmosphere, pyrolyze for 3 to 4 hours, cool, and grind to obtain a black powdery nitrogen-doped carbon-loaded iron material, referred to as Fe-NC.

2. The method for preparing the nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 1, characterized in that: The stirring time of step 1 and step 2 is 10 to 30 minutes.

3. The method for preparing the nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 1, characterized in that: The stirring time of step 3 is 2 to 3 hours.

4. The method for preparing the nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 1, characterized in that: The centrifugation in step 3 is carried out using a centrifuge at a speed of 5000 rpm for 10 minutes.

5. The method for preparing nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 1, characterized in that: The centrifugal washing in step 3 is performed by using a centrifuge with a speed of 5000 rpm, and washing the precipitate with anhydrous methanol for 4 to 5 times, each washing lasting 10 minutes.

6. The method for preparing nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 1, characterized in that: The drying in step 3 is carried out in an oven at 60° C. for 12 hours.

7. A nitrogen-doped carbon-supported iron material for adsorbing BPA prepared by the method according to any one of claims 1 to 5, characterized in that: At 25℃, the maximum adsorption capacity of BPA in water is 877.45 mg·g -1 .

8. The nitrogen-doped carbon-loaded iron material for adsorbing BPA according to claim 7, characterized in that: The removal rate of BPA in water is greater than 90% during the 10-minute adsorption process.